Pengaruh Motivasi Belanja Hedonis terhadap Pembelian Kompulsif - Nur Rizka Luffiana; Harmanda berima putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of hedonic shopping motivation on compulsive buying. This research data collection method uses primary data. The population used in this research is consumers who have shopped at Transmart. This research uses purposive sampling technique while the sample size in this research is 170 respondents. This research model uses the Structural Equation Modeling (SEM) Partial Least Square (PLS). The results showed that shopping for ideas and social shopping have a positive effect on compulsive buying. Meanwhile, satisfaction seeking, adventure seeking, role shopping and shopping value do not have a significant effect on compulsive buying.